Calculation of the equivalent electrical parameters of the inductor of induction channel furnace with defects in its lining - Podoltsev, O. D.; Zolotaryov, V. M.; Shcherba, M. A.; Belyanin, R. V. (НТУ "ХПИ", 2018)
The aim of the paper is to determine a quantitative relationship between measured impedance of the inductor and the electrical characteristics of the separated melt circuit parts for the determination of the place of a liquid metal leakage andfor the improvement in such way the diagnostic system of lining state of induction channel furnaces. The study was performed on the basis of the concepts of theoretical electrical engineering, mathematical physics, and mathematical modeling. Using two equivalent electrical circuits of the inductor the analytical expressions and graphical dependencies, which determine a quantitative relationship between the parameters of the separated parts of a liquid-metal circuit and the impedance of the whole inductor measured in practice, for the presence of different lining defects, were found. The method for calculating the increments of equivalent electrical parameters of the inductor as a function of increments of the parameters of the secondary liquid-metal circuit was proposed. It is proved that for small changes (less than 10 %) of the parameters of the liquid-metal circuit, it is expedient to use a linear relationship between its increments and to create the sensitivity matrix, which clearly shows the presence of a strong or weak interrelation between the disturbed values of the parameters of the secondary circuit and the inductor. The use of this technique allows to develop the database for various types of lining defects for a given furnace and on itsbasis to predict the places of a melt leakage and the state of furnace lining owing to periodical measurements of the inductor parameters.

Целью статьи является установление количественной связи между измеряемым импедансом индуктора и электрическими характеристиками отдельных участков контура расплава для установления места протекания жидкого металла и усовершенствования таким образом системы диагностики состояния футеровки индукционных канальных печей. Для проведения исследований использовались положения теоретической электротехники, математической физики, математического моделирования. C использованием двух электрических схем замещения индуктора получены аналитические выражения и графические зависимости, устанавливающие количественную связь между параметрами отдельных участков жидкометаллического контура и измеряемым на практике импедансом всего индуктора при наличии различных дефектов в его футеровке. Предложена методика расчета приращений эквивалентных электрических параметров индуктора в зависимости от приращений параметров вторичного жидкометаллического контура. Доказано, что при малых изменениях (менее 10%) параметров жидкометаллического контура целесообразно использовать линейную связь между их приращениями с построением матрицы чувствительности, которая наглядно показывает наличие сильной или слабой связи между возмущенными значениями параметров вторичного контура и индуктора. Использование данной методики позволяет разработать базу данных для различных типов дефектов футеровки для индукционной канальной печи и на ее основе, путем периодического измерения параметров индуктора, прогнозировать места протеканий расплава и состояние футеровки.
Keywords: mathematical modeling; defects of lining; electrical characteristics; liquid metal; эквивалентные электрические параметры; математическое моделирование; индукционная канальная печь; дефекты футеровки; диагностика состояния футеровки